Identification of static distortion by noise measurement. Issue 21 (1st October 2013) - Gunn, L.J.; Allison, A.; Abbott, D.
Abstract : Many active devices exhibit gross nonlinearity, which is traditionally mitigated using negative feedback. In those cases where negative feedback is not desired, compensation for the distortion can be carried out at the postprocessing stage by inverting the transfer function of the device. A new technique is demonstrated where the inherent noise in the system is exploited to estimate the required transformation, thus reducing distortion without the need for an offline characterisation step. It is demonstrated that the proposed technique can reduce the total harmonic distortion of a common‐emitter amplifier from about 10% to < 1%.